Demonstration of the synergistic effect of biochar and Trichoderma harzianum on the development of Ralstonia solanacearum in eggplant - Ahmad, Chaudhry Ali; Akhter, Adnan; Haider, Muhammad Saleem; Abbas, Muhammad Taqqi; Hashem, Abeer; Avila-Quezada, Graciela Dolores; Abd_Allah, Elsayed Fathi (Frontiers in Microbiology, 2024)
Soil degradation has been accelerated by the use of chemical pesticides and poor agricultural practices, which has had an impact on crop productivity. Recently, there has been a lot of interest in the use of eco-friendly biochar applications to enhance soil quality and sequester carbon in sustainable agriculture. This study aimed to determine the individual and combined effects of Leaf Waste Biochar (LWB) and the bio-control agent Trichoderma harzianum (BCA) on the development of bacterial wilt in eggplants (Solanum melongena) caused by Ralstonia solanacearum (RS). The effects of LWB and BCA on eggplant physiology and defense-related biochemistry were comprehensively examined. Inoculated (+RS) and un-inoculated (–RS) eggplants were grown in potting mixtures containing 3% and 6% (v/v) LWB, both with and without BCA. The percentage disease index was considerably reduced (90%) in plants grown in the 6% LWB+ BCA amended treatments. Moreover, the plants grown in LWB and inoculated with BCA had higher phenolics, flavonoids and peroxidase contents compared to the non-amended control. The level of NPK was significantly increased (92.74% N, 76.47% P, 53.73% K) in the eggplants cultivated in the 6% LWB + BCA composition. This study has shown that the association of T. harzianum with biochar improved plant growth and reduced R. solanacearum induced wilt. Furthermore, the combined impact of biochar and T. harzianum was greater in terms of wilt suppression and increase in plant physiological measurements when the biochar concentration was 6%. Biochar and bio-control agents triggered biochemical alterations, thus enhancing the management of disease-infested soils.